Effectiveness of Sharia Services and Buying Experience in Retail MSMEs Consumer Loyalty - Fatimah, Feti; Hermawan, Haris (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This research is intended to determine the role of sharia services and buying experience on Consumer Loyalty in Retail MSMEs. This research was conducted qualitatively based on descriptive. The data collection process uses interview techniques to collect information about the role of sharia services and buying experience on retail MSME consumer loyalty. The object of research is Retail SMEs in Jember Regency. The results of the interviews were analyzed descriptively according to the facts and perspectives of researchers related to the problem of consumer loyalty. The output of this research is the role model of sharia services based on buying experience to foster consumer loyalty of Retail MSMEs. The results of the research conclude that to grow consumer loyalty, one must pay attention to sharia services that are in accordance with the needs and desires of the intended consumers, namely sharia services and buying experience because an impressive shopping experience will make consumers want to shop again at the Retail MSMEs. Sharia services based on buying experience on consumer loyalty is a new concept in marketing management research and provides a better explanation of consumer behavior. The results of this study are taken into consideration for Retail MSMEs, where the impact of the Covid-19 pandemic requires innovation in providing services, including sharia services and buying experience.